Zinc Supplementation in Children with Acute Diarrhea - Shehla Choudhry, Parveen Akhtar Tariq, Ayesha Afzal (Journal of Rawalpindi Medical College, 2009)
Background: To evaluate the effect of zinc supplementation on the outcome of acute diarrhea by comparing it with standard management of acute diarrhea in children. Methods: In this interventional study, total 100 patients, 6 months to 5 years of age were enrolled and were randomly allocated in Group A or Group B . Group A was treated with standard management of acute diarrhoea whereas Group B was given zinc supplementation in addition to standard management protocols. Children were monitored for stool frequency, consistency , state of hydration and any complicating factor. Results: The frequency of stools in group A and B reduced from 16.1 + 4.4 8 stools/day and 15.66+ 4.24 stools/day to 6.80+ 1.99 stools/day and 1.78+ 1.79 stools/day respectively. The consistency of stools in group A and B changed from 3.9 and 3.8 on day one to 2.14 and 1.68 , respectively , on day 7. Conclusion: The zinc supplementation had no effect on the outcome of acute diarrhoea in children. There was no significant reduction in the severity of acute diarrhoea in the children who were given the zinc supplements, in comparison to those who were managed with the standard treatment protocol.